Implementation Of Criminal Sanctions Against Companies Violating Provincial Minimum Wages From The Perspective Of John Rawls' Theory Of Justice - Dedy Cahyadi; Bambang Soesatyo (al-Battar: Jurnal Pamungkas Hukum, 2025)
Violation of the Provincial Minimum Wage (UMP) provisions by companies is still a labor problem in Indonesia. Although there are regulations governing the obligation of companies to pay minimum wages and criminal sanctions for violators, implementation in the field still shows many obstacles, such as weak supervision, low deterrent effect of sanctions, and legal loopholes that allow companies to avoid these obligations. This study uses a normative legal method with a statutory and conceptual approach to analyze the effectiveness of criminal sanctions against companies that violate the UMP based on John Rawls' Theory of Justice. The results show that the existing sanction system does not fully reflect the principle of substantive justice because it does not provide maximum protection for the most vulnerable workers (least advantaged). Therefore, reforms are needed in the law enforcement system, including increasing the capacity of labor inspectors, implementing stricter sanctions based on the company's economic scale, and direct compensation mechanisms for workers who experience violations. Thus, the implementation of the UMP policy can better reflect the principles of social justice and fair distribution from the Rawlsian perspective